2013
DOI: 10.1007/s00414-013-0933-5
|View full text |Cite
|
Sign up to set email alerts
|

Fetal age estimation using MSCT scans of the mandible

Abstract: The purpose of this study was to examine a documented fetal collection, to carry out morphometric analysis of femoral length and of the mandible, and to develop diagnostic standards for estimating fetal age at death based on multislice computed tomography (MSCT) reconstructions. The sample was composed of 81 fetuses, whose ages were recorded in weeks of amenorrhea (WA) between 20 to 40 WA. The measurements made were femoral length (FL) and six distances and four angles of the mandible. Femoral length was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This sample was collected in a prenatal diagnostic center, which under French law, is permitted to study anonymous fetopathological records. This collection has been the basis of several studies (12)(13)(14). The fetuses were fixed with 10% formalin and then vacuum packed.…”
Section: Subjectsmentioning
confidence: 99%
“…This sample was collected in a prenatal diagnostic center, which under French law, is permitted to study anonymous fetopathological records. This collection has been the basis of several studies (12)(13)(14). The fetuses were fixed with 10% formalin and then vacuum packed.…”
Section: Subjectsmentioning
confidence: 99%
“…Research comparing traditional measurement methods to obtain fetal age is quite scarce, since current tendencies include looking for new and modern techniques to estimate fetal age, however not always available (Minier et al, 2014a;2014b;Pomier et al, 2019). It is necessary to compare the traditional methods in order to find out which is the most accurate in cases where the gold standard cannot be used and no modern technologies to perform these measurements are available.…”
Section: Introductionmentioning
confidence: 99%
“…A pair of studies were made using Multiple Slide Computed Tomography (MSCT) technology, which found that it is possible to calculate the fetal age by evaluating the deciduous tooth gems or the mandible, obtaining a reliable result compared to the measurement of the femoral diaphyseal length (Minier et al, 2014a;2014b). However, calculating the fetal age with this method may not always be possible, particularly in cases where an MSCT is not available.…”
Section: Introductionmentioning
confidence: 99%
“…Usually to investigate these issues experimental models are used (laboratory animals) [1]. The methods of development and analysis of two-dimensional reconstructions are applied at the late stages of the craniofacial human development [2]. The data concerning regulations and peculiarities of mandibular morphogenesis during the prenatal period of human ontogenesis are insufficient.…”
Section: Introductionmentioning
confidence: 99%